MULTI-CROP LAND SUITABILITY ASSESSMENT USING GIS–AHP IN OSUN STATE, NIGERIA - OLUWADARE, Caleb Olutayo; EYINADE, John Adeyemi; ABIDOYE, Ayodeji Iyanu; OGUNLANA, Bolaji Samuel; OLUWADARE, Joshua Ayodeji (Studia Universitatis Babeș-Bolyai Geographia, 2025)
The sustainable cultivation of arable crops in Nigeria is increasingly challenged by climate variability, land degradation, and inefficient land use practices. This study evaluates the land suitability of Osun State for multiple crops—cassava, maize, yam, rice, cocoa, plantains, and vegetables—using a GIS-based Analytical Hierarchy Process (AHP) approach. The research has been conducted to produce spatially explicit suitability maps to support climate-resilient agricultural planning and optimization of crop selection in the region. Seventeen environmental, climatic, and edaphic criteria-slope, elevation, rainfall, temperature, soil pH, organic carbon, macro-nutrients, proximity to roads, and rivers-were integrated using AHP, which derives weights from expert judgment. The weights were then used in a weighted overlay analysis to map the area according to the suitability classes: highly suitable, suitable, moderately suitable, marginally suitable, and unsuitable. The results revealed that cassava and maize have the highest proportions of highly suitable land in the state, with yam coming next. Spatial analysis sets out the top Local Government Areas such as Aiyedaade, Ife South, Ife North, Atakumosa West, and Obokun as highly preferable zones for multi-crop cultivation. This study draws attention to the usefulness of the GIS–AHP method for land evaluation at the regional scale and provides critical insight into data-driven agricultural policy, sustainable land use, and food security in sub-Saharan Africa.